2020
DOI: 10.1007/s10680-020-09568-8
|View full text |Cite
|
Sign up to set email alerts
|

Are the Sick Left Behind at the Peripheries? Health Selection in Migration to Growing Urban Centres in Finland

Abstract: We study health selection in rural–urban migration in Finland using register data. Specifically, we ask whether ‘movers’ differ from ‘stayers’ in their use of special health care services prior to moving. We focus on migration to twelve growing urban centres in different sub-groups of the population as well as in different regions, using multinomial logistic regression and multilevel modelling and by distinguishing between short- and long-distance moves. The results show that urban centres attract healthier in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Selective migration can affect regional composition and socioeconomic contexts, and also affects the associations between urbanicity and psychotic disorders [ 5 , 10 , 39 , 40 ]. In Finland, however, it has been suggested that individuals with mental disorders are not particularly likely to move to the most urban centers [ 41 ], and accessibility of Finnish primary health care is mostly at good level, although in a recent study, travel time in rural areas negatively associated with primary care mental health service use [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selective migration can affect regional composition and socioeconomic contexts, and also affects the associations between urbanicity and psychotic disorders [ 5 , 10 , 39 , 40 ]. In Finland, however, it has been suggested that individuals with mental disorders are not particularly likely to move to the most urban centers [ 41 ], and accessibility of Finnish primary health care is mostly at good level, although in a recent study, travel time in rural areas negatively associated with primary care mental health service use [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selective migration can affect regional composition and socioeconomic contexts, and also affects the associations between urbanicity and psychotic disorders (Colodro-Conde et al, 2018;Krabbendam et al, 2021;Pedersen, 2015;Sariaslan et al, 2016). In Finland, however, it has been suggested that individuals with mental disorders are not particularly likely to move to the most urban centers (Vaalavuo & Sihvola, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many countries experience a brain-drain of highly educated persons away from economically disadvantaged regions to prosperous urban centers (Dahl, 2002;Diamond, 2016;Greenwood, 1997). Such a brain drain can be accompanied by a health drain if persons who move for example from rural to urban regions are positively selected on health, as Vaalavuo and Sihvola (2021) show for the case of Finland. Such a health drain might have a noticeable impact on healthcare costs and needs in peripheral or economically disadvantaged regions not just in the Netherlands, but also in other countries.…”
Section: Introductionmentioning
confidence: 87%